Effect of preoperative pulse oximeter oxygen saturation on postoperative prolonged mechanical ventilation in patients with tetralogy of Fallot - Wu, Xie; An, Ran; Luo, Qipeng; Li, Yinan; Wang, Hongbai; Liu, Qiao; Huang, Jiangshan; Jia, Yuan; Yuan, Su; Yan, Fuxia (Frontiers in Cardiovascular Medicine, 2022)
Background As an easily accessible and intervened clinical indicator, preoperative pulse oximeter oxygen saturation (SpO2) is an important factor affecting the prognosis of patients with tetralogy of Fallot (TOF). However, whether SpO2 is associated with postoperative mechanical ventilation (MV) time remains unknown. Therefore, this study aimed to investigate the impact of preoperative SpO2 on postoperative prolonged mechanical ventilation (PMV) in children with TOF. Materials and methods The study included children younger than 18 years who underwent corrective operations for TOF between January 2016 and December 2018 in Fuwai Hospital, China. Univariate and multivariate logistic regression analyses were used to evaluate the influence of preoperative SpO2 on postoperative PMV. After identifying SpO2 as an independent risk factor for PMV, patients were further divided into two groups according to the cutoff value of SpO2, and propensity score matching (PSM) analysis was used to eliminate the effect of confounding factors. The logistic regression was used to compare the outcomes between the two groups after PSM. Results A total of 617 patients were finally enrolled in this study. By the univariable and multivariate logistic analysis, four independent risk factors for PMV were determined, namely, SpO2, surgical technique, aortic cross-clamp time, and intraoperative minimum temperature. According to the outcomes of 219 paired patients after PSM, the incidence of PMV was significantly higher in patients with lower preoperative SpO2 (P = 0.022). Also, there was significant increase in mechanical ventilation time (P = 0.019), length of intensive care unit stay (P = 0.044), postoperative hospital stay (P = 0.006), hospital stay (P = 0.039), and hospitalization cost (P = 0.019) at the lower preoperative SpO2 level. Conclusion Low preoperative SpO2 represents an independent risk factor of postoperative PMV in children with TOF.